Environmental quality evaluation of lakes in the Rio Grande do Sul coastal plain - Pedrozo,Catarina da Silva (2007)
The purpose of the present work was to evaluate the environmental quality of Marcelino, Pinguela, Peixoto, Palmital, Malvas and Do Passo lakes, interconnected by canals and located in the district of Osório, RS. In this context, 29 physical and chemical variables were analyzed with sampling carried out in January, May, July and October 1997 to verify the environmental quality of the system and the existence of a gradient of quality. Canonical Analysis was applied to the data of all environmental variables measured, and showed that the lakes had different characteristics as a consequence of the organic pollution received. Marcelino lake received continuous input of organic matter from the sewage treatment works in the town of Osório, whereas Peixoto, Pinguela, Palmital, Malvas and Do Passo lakes resembled other water bodies described in the region, not showing, so far, signs of degradation caused by the input of effluents. Principal Component Analysis selected environmental element were directly linked to organic pollution, that reflected sequential non-recent effects of contamination.